Phospholipase D Signaling Mediates Reactive Oxygen Species‐Induced Lung Endothelial Barrier Dysfunction. (1st January 2013) - Usatyuk, Peter V.; Kotha, Sainath R.; Parinandi, Narasimham L.; Natarajan, Viswanathan
Abstract : Reactive oxygen species (ROS) have emerged as critical players in the pathophysiology of pulmonary disorders and diseases. Earlier, we have demonstrated that ROS stimulate lung endothelial cell (EC) phospholipase D (PLD) that generates phosphatidic acid (PA), a second messenger involved in signal transduction. In the current study, we investigated the role of PLD signaling in the ROS‐induced lung vascular EC barrier dysfunction. Our results demonstrated that hydrogen peroxide (H2 O2 ), a typical physiological ROS, induced PLD activation and altered the barrier function in bovine pulmonary artery ECs (BPAECs). 1‐Butanol, the quencher of PLD, generated PA leading to the formation of physiologically inactive phosphatidyl butanol but not its biologically inactive analog, 2‐butanol, blocked the H2 O2 ‐mediated barrier dysfunction. Furthermore, cell permeable C2 ceramide, an inhibitor of PLD but not the C2 dihydroceramide, attenuated the H2 O2 ‐induced PLD activation and enhancement of paracellular permeability of Evans blue conjugated albumin across the BPAEC monolayers. In addition, transfection of BPAECs with adenoviral constructs of hPLD1 and mPLD2 mutants attenuated the H2 O2 ‐induced barrier dysfunction, cytoskeletal reorganization and distribution of focal adhesion proteins. For the first time, this study demonstrated that the PLD‐generated intracellular bioactive lipid signal mediator, PA, played a critical role in the ROS‐induced barrier dysfunction in lung vascular ECs. This study also underscores the importance of PLD signaling in vascular leak and associated tissue injury in the etiology of lung diseases among critically ill patients encountering oxygen toxicity and excess ROS production during ventilator‐assisted breathing.